Genetic variability among sorghum accessions for seed starch and stalk total sugar content (Scientia Agricola, 2014)
Sorghum (Sorghum bicolor (L.) Moench) is a staple food grain in many semi-arid and tropical areas of the world, notably in sub-Saharan Africa because of its adaptation to harsh environments. Among important biochemical components for sorghum for processors are the levels of starch (amylose and amylopectin) and total sugar contents. The aim of this study was to determine the genetic variation for total starch in the seed, its components and total sugar in the stalks of the sorghum accessions from Ethiopia and South Africa. Samples of 22 sorghum accessions were evaluated. Significant variations were observed in total starch (31.01 to 64.88 %), amylose (14.05 to 18.91 %), the amylose/amylopectin ratio (0.31 to 0.73) and total stalk sugar content (9.36 to 16.84 %). Multivariate analysis showed a wide genetic variation within and among germplasm accessions which could be used in the selection of parental lines for the improvement of traits of interest through breeding. The variation found among the sorghum accessions shows that an improved total starch and starch components and stalk sugar contents can be achieved through crossing these selected genotypes.